Correlation of venous clinical severity score and venous disability score with dermatology life quality index in chronic venous insufficiency - Subhadeep Mallick; Tanusree Sarkar; Tirthankar Gayen; Biswanath Naskar; Adrija Datta; Somenath Sarkar (Wolters Kluwer Medknow Publications, 2020)
Background: Chronic venous insufficiency (CVI) is an underestimated public health problem involving the lower limbs. It exerts a significant impact on patient's quality of life (QoL). The severity of the disease was measured by venous clinical severity score (VCSS) and venous disability score (VDS). Aims: The aim of the study was to evaluate VCSS, VDS, and dermatology life quality index (DLQI) among the patients of CVI and to evaluate the correlation among DLQI with VCSS, VDS, and leg ulcer. Materials and Methods: In this institution-based cross-sectional study, clinically and sonographically confirmed cases of CVI were included. Clinical severity of the disease and disability were assessed by using VCSS and VDS, respectively. QoL was assessed by a validated DLQI questionnaire. Correlation between DLQI with VCSS and VDS was analyzed. The association between DLQI with different characteristics of the ulcer was also evaluated. Results: Mean VCSS, VDS, and DLQI in the study population were 11 ± 4.96, 1.47 ± 0.67, and 6.94 ± 3.87, respectively. Both VCSS and VDS had a strong positive correlation with DLQI. The number of active ulcers, size of the ulcer, and duration of the ulcer had a strong positive correlation, whereas the age of onset of the disease had a negative correlation and duration of the disease had poor correlation with DLQI. Pain (P = 0.03) and edema (P = 0.04) had significant association with VDS. Conclusion: VCSS and VDS are important tools for measuring severity and disability in CVI, respectively. CVI had a strong impact on patients QoL more than it was thought hitherto.